Real-time tracking of carbon corrosion by atomic force microscopy reveals the impact of defect topography on degradation dynamics - Austin J. Reese; Jingzhi Hu; Jin Suntivich (Proceedings of the National Academy of Sciences, 2026)
Carbon materials are widely deployed in electrochemical energy technologies; however, the nanoscale mechanisms underlying their durability remain incompletely understood. We report the visualization of the corrosion dynamics of highly oriented pyrolytic graphite in aqueous acidic environments using in situ atomic force microscopy. By tracking topography in real time, we correlate local corrosion kinetics with specific defect classes. Three salient findings emerge: i) corrosion preferentially occurs through point and line defects, ii) the corrosion rate at individual defects scales with applied potential, and iii) deeper defects propagate more slowly. We further show that corrosion rates are faster when originating from defects than from bulk carbon. These results demonstrate that defects govern corrosion susceptibility in highly crystalline carbon and that the corrosion propagation rate depends on defect geometry. Our findings provide evidence of defect-mediated corrosion in carbon materials and reveal how defect geometry dictates corrosion dynamics, linking nanoscale heterogeneity to electrochemical durability.